2019
DOI: 10.4236/aim.2019.97036
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Analysis and Public Health Impact of Broiler Meat: A Study on Nalitabari Paurosova, Sherpur, Bangladesh

Abstract: Broiler meat is one of the most important protein sources for Bangladeshi people. Food-borne diseases associated with the consumption of poultry meat and its processed products are of public health concern worldwide. An investigation was conducted to assess the bacteriological quality of poultry meat from some poultry farms and its health impact on consumer of Nalitabari paurosova, Sherpur district, Bangladesh. Total 15 samples were randomly selected and collected from different poultry farms on the basis of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…The present study reports the first comprehensive findings on the extent and distribution of ESBL-Ec and their antimicrobial resistance pattern including resistance genes in frozen chicken meat collected from almost all branded supershops located in five megacities of Bangladesh. This study showed the high prevalence (76.1%) of E. coli in frozen chicken meat compared with 49-53% prevalence in raw chicken meat as reported earlier in Bangladesh [30,31], 66.3% in India [32], 47.1% in Nepal [33], and 50.5% in Korea [34], and this may be a potential hazard to the consumers. The difference in the prevalence of E. coli may be attributed to several factors including the source of meat, sample number, isolation methods, possible cross-contamination during slaughtering, slaughterhouse sanitation, and personal hygiene, as well as other practices through to the food chain.…”
Section: Discussionsupporting
confidence: 75%
“…The present study reports the first comprehensive findings on the extent and distribution of ESBL-Ec and their antimicrobial resistance pattern including resistance genes in frozen chicken meat collected from almost all branded supershops located in five megacities of Bangladesh. This study showed the high prevalence (76.1%) of E. coli in frozen chicken meat compared with 49-53% prevalence in raw chicken meat as reported earlier in Bangladesh [30,31], 66.3% in India [32], 47.1% in Nepal [33], and 50.5% in Korea [34], and this may be a potential hazard to the consumers. The difference in the prevalence of E. coli may be attributed to several factors including the source of meat, sample number, isolation methods, possible cross-contamination during slaughtering, slaughterhouse sanitation, and personal hygiene, as well as other practices through to the food chain.…”
Section: Discussionsupporting
confidence: 75%
“…The present study reports the first comprehensive findings on the extent and distribution of ESBL-Ec and their antimicrobial resistance pattern including resistance genes in frozen chicken meat collected from almost all branded supershops located in five megacities of Bangladesh. This study showed the high prevalence (76.1%) of E. coli in frozen chicken meat compared with 49-53% prevalence in raw chicken meat as reported earlier in Bangladesh [25,26], 66.3% in India [27], 47.1% in Nepal [28] and 50.5% in Korea [29], and this may be a potential hazard to the consumers. The prevalence of E. coli may be attributed to several factors including source of meat, sample number, isolation methods, possible cross contamination during slaughtering, slaughterhouse sanitation as well as personal hygiene, and other practices through to the food chain.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have reported that Salmonella isolated from poultry in Bangladesh were sensitive to ciprofloxacin [ 37 , 42 , 43 ]. However, in the present study, Salmonella isolates were found to be susceptible to ampicillin, piperacillin/tazobactam, nitrofurantoin, imipenem and amikacin, as was previously reported [ 39 ].…”
Section: Discussionmentioning
confidence: 99%